Perancangan Sistem Informasi Akuntansi Persediaan Bahan Baku di CV Anugerah Sukses Gemilang - Ai Ida Parida; Syifa Nurlaelasari; Muthmainnah; Falaah Abdussalaam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The raw material inventory recording system at CV Anugerah Sukses Gemilang is still done manually, therefore errors often occur in recording raw material inventory and it takes a long time to record raw material inventory manually. This causes the reports presented to be less accurate and take a long time to make reports in each period. This system is designed using Microsoft Visual Studio 2010 by utilizing the VB.Net and MYSQL database. The purpose of this research is to be able to manage raw material inventory computerized and to present accurate and automatic reports in each period. The research method used consisted of data collection methods based on observations, interviews and literature studies. The system development method used is the waterfall method. The results of this study are in the form of applications that help simplify and speed up officers in recording raw material inventories, especially in terms of data reporting.